A study to assess the principle based practices of primary health care among primary health workers of PHC in urban and rural areas of Navi Mumbai - Prasad, Sudershna (Indian Journal of Nursing Sciences, 2024)
The Bhore committee in 1946 recommended an integrated health services comprising primary health care and other levels of care.”Primary health care is an essential health care based on practical , scientifically sound and socially acceptable methods and technology made universally accessible to individual and families in community through their full participation and at a cost that the community and country can afford to maintain at every stage of their development in the spirit of self reliance and self determination”. The research was conducted on the statement “A study to assess the principle based practices of primary health care among primary health workers of PHC in urban and rural areas of Navi Mumbai.” The study is a non-experimental comparative research design. The study conducted was on 50 samples in urban and 50 samples in rural population. Before the main study a pilot study was conducted on 20 samples. The findings of the pilot study were analyzed by mean and frequency. The study design was then found to be feasible and convenient for main study. A self-structured interview schedule was prepared and used for data collection. Data was analyzed using descriptive and inferential statistics like frequency and percentage, mean and standard deviation. The results show that the primary health care workers in rural area provide better principle based primary health care as compared to the primary health care workers in urban area.